PENGARUH PENGGUNAAN DIGITAL BANKING SEBAGAI LAYANAN TRANSAKSI ONLINE TERHADAP KEPUASAN NASABAH BANK BSI SYARIAH KABUPATEN LANGKAT - Nurhayani, Nurhayani; Kamilah, Kamilah; Bi Rahmani, Nur Ahmadi (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine the extent to which accuracy (X1), speed (X2), security (X3) influences customer satisfaction (Y). This study uses a quantitative approach with sampling using the Non Probability Sampling method. The type of data used in this study is primary data obtained from questionnaires filled out by respondents directly. While secondary data comes from books, journals, research results, practical work reports and related to the author's research object. In this study, the population that will be taken is all BSI Syariah customers in Langkat Regency from 2020 to February 2022, namely 30,100 customers. The analysis tool uses multiple linear regression analysis. The results of the study show that accuracy (X1), speed (X2), security (X3) simultaneously affect customer satisfaction (Y). Keyword: Accuracy, Speed, Security, Customer Satisfaction.